(untitled) (Journal of Hama University, 2020)
The Present study was designed to evaluate the effect of fentanyl on some blood parameters and note some vital reflexes(Heart rate ,analgesia, absence of sensory reflexes ,respiratory rate and temperature degree)which are shown by dogs during injection and after injection. For this purpose ,six dogs with no breed of about 7-9 kg body weight and Aged between 3-4 years where blood samples were taken before injection then injected intravenously with fentanyl after that blood samples were taken after 15,30,60,120 minutes and after 24 hour. Then sensory reflexes are recorded according to previous intervals. As a result , heart rate ,respiratory rate showed significant decrease (P<0.05) at time 15,30 minutes while, no significant changes of body temperature after administration. The hematological Parameters Hb ,PCV, blood platelets and RBC showed significant decrease (P<0.05) after injection of fentanyl at time 30,60 minutes while, no significant changes of White blood cell̦̦̦̦s There were significant decrease (P<0.05) in serum enzymatic activities of (ALT,AST, CPK, ALP , GGT) at time15,30. 60 minutes after administration. Sodium and Potassium showed a significant decrease (P<0.05) at time 15,30 minutes. No significant changes in concentrations of Calcium , Chloride and Magnesium . Albumin showed significant decrease (P<0.05) at time 15,30 minutes while Glucose showed significant increase at that time but creatinine showed significant decrease at time 15,30 and 60.